Pengaruh Logoterapi Kelompok terhadap Kemampuan Memaknai Hidup pada Residen Napza - Sutejo Sutejo (Alma Ata University Press, 2017)
Drug abuse is ineffective coping behavior in resolving stress conditions. There are several psychological problems affecting the meaning of life's crisis such as: low self-esteem, lack of motivation, feeling powerless, desperation, and suicide risk. Group Logotherapy is a psychotherapy which can assist to evoke optimism of a humankind in facing the future after all obstacles encountered. The purpose of this study was to investigate the influence of group logotherapy on the drug users' resident in interpreting the meaning of life's ability at Pamardi Putra Rehabilitation Center of Yogyakarta Social Agency. This study method was a quasi-experiment pretest-posttest with control group design was conducted at Permadi Putra Social Rehabilitation Center of Yogyakarta. Random sampling method applied to select the samples. All 44 samples were recruited and divided into two groups for both experimental group (22 samples) and control group (22 samples). Group Logotherapy by using Value Awareness Technique (VAT) concerned as Independent variable and Life's Meaning categorized as dependent variable. The Meaning in Life's questionnaire was applied to this study. Wilcoxon Signed Rank Test was attempted to analyzed the data with 5% significant value (p=0,05). Results showed that the average result value for both pretest and posttest on the control group is 13,32 and 17,00 with (p-value=0.000.05). In conclusion, the statistical analysis was found significant different result between both control and experimental groups on the drug resident users about their life's meaning at Pamardi Putra Rehabilitation Center of Yogyakarta Social Agency.